Analysis of adaptation processes and anxiety levels of university students staying with earthquake survivor families in state dormitories - İbrahim Dağ; Kadriye Olğaç (BMC Psychiatry)
Abstract Background This study aimed to examine the adaptation processes and anxiety levels of university students living with earthquake survivor families placed in state dormitories after recent major earthquakes. Materials and Methods A descriptive, cross-sectional quantitative study was conducted in a state dormitory between May and August 2023. A total of 108 students participated using the snowball sampling method. Data were collected through a Descriptive Characteristics Form and the Beck Anxiety Scale. Statistical analyses included descriptive statistics and linear regression using SPSS 25.0. Results Among the participants, 49% reported increased frequency of contact with their families after the earthquake. Sharing the same dormitory space with earthquake-affected families led to limited personal space for 56%, emotional impact for 51%, and benefits such as emotional support for 56%. Additionally, 45% noted changes in their attitudes, 46% in their social lives, and 56% in their social responsibility awareness. Regression analysis showed that sharing the same environment with families explained 33.7% of the variance in Beck anxiety scores. A significant positive relationship was found between cohabitation with families and anxiety levels (B=0.337, p<0.001), where each unit increase in cohabitation was associated with a 5.379-point increase in anxiety scores. Conclusions The findings indicate that post-earthquake family cohabitation significantly affects students' psychological and social well-being. Living in close proximity to affected family members increases anxiety levels. Providing psychological support services for students is crucial to reduce anxiety and facilitate post-disaster recovery and adaptation.